Management and Outcome of a Neurologically Intact Infant with Pierre Robin Sequence and Dandy-Walker Variant Diagnosed with Large Hemispheric Brain Abscess – Case Report - Jamous, Mohammad A.; Alomari, Amer A.; Jbarah, Omar F. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Pierre Robin sequence (PRS) is a condition consisting of three essential components: micrognathia or retrognathia, cleft palate, and glossoptosis. It can be part of multiple congenital anomalies. We present the case and outcome of a 3-month-old clinically stable patient who has PRS with Dandy-Walker variant – which is a rare presentation in the literature – with a large right hemispheric brain abscess, treated with multiple minimally-invasive surgical drainage procedures with adjuvant antibiotics.
Keywords: Pierre Robin sequence; Dandy-Walker variant; brain abscess